Factors Influencing Arrest Decision-Making in Domestic Violence Cases in Zambia - Nakena Likando; Simona Simona (Archives of Current Research International, 2023)
Domestic violence is among the most prevalent forms of violence globally. It includes physical violence, emotional violence, sexual violence and economic violence. Several studies focusing on arrest decisions are conducted in the West; unfortunately, there is a dearth of studies focusing on domestic violence in Zambia especially on factors that influence arrest decision-making. This study was conceived to examine whether legal and extra-legal factors have an influence on the Zambia police service officers’ decision-making in domestic violence cases reported to them. Data consisting of 1258 cases of domestic violence from 2017-2019 were collected from five urban police stations in Lusaka city. In this study, we used univariate, bivariate and multiple logistic regression analysis to examine police officers’ decision-making in domestic violence cases. Descriptive results show that arrest rates are high in physical violence (13.20%), economic violence (9.46%), sexual violence (5.41%) and emotional violence (3.18%). Whilst the age of the victim, perpetrator ethnicity and the gender of police officers were found to be non-significant, strong predictors of arrest decision-making in a logistic analysis were found to be victim tribe, residential area, perpetrator age and type of domestic violence. Policy strategies and efforts should be channelled towards advocacy and awareness programmes across the communities and should not neglect the participation of victim support unit (VSU) police officers. Therefore, the Victim support unit should be appropriately funded to enhance awareness campaigns and educational programmes. Additionally, the police command should find ways of navigating around victims’ preferences in arrest decisions whilst respecting and upholding human rights and ethical standards.